Exploring The Utilization of Micro-Loans among Livestock Farmers - Jure, Roshell U.; Magsayao, Shela Mae C.; Tan, Kent Jasper L.; Sumicad Jr., Eligen H.; Batingal, Ace Virgel T. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study explores how microloans are helping livestock farmers in Pagadian City, Zamboanga del Sur, Philippines. For many small-scale farmers, traditional banks are out of reach microloans fill that gap by offering accessible financing to support their agricultural activities. These loans have become a valuable tool for rural development, giving farmers a chance to invest in their farms, improve productivity, and increase income. To understand how microloans are used and how effective they are, the study combined survey responses and interviews with local farmers, along with insights from microfinance institutions. It looked into how loans are approved, how they're used, and what challenges farmers face particularly with repayment and access to reliable information. The findings show that microloans have made a real difference. Farmers used the funds to buy healthier livestock, upgrade their facilities, and improve overall farm output. But not everything worked perfectly. Some struggled with strict repayment terms, and others didn’t fully understand how to access or manage these financial tools. The study offers practical recommendations for policymakers, lenders, and farmers. These include introducing more flexible repayment options, improving farmer education about loan programs, and encouraging better coordination between lenders and agricultural support services. This research provides meaningful insights into how microloans can be made more effective. It points the way toward smarter policies and programs that can help small farmers thrive and contribute more fully to sustainable rural development.